Мixed anxious and depressive reaction during adaptation disorder in participants during anti-terrorist operation - Kateryna Semenenko (Kazimierz Wielki University, 2022)
Adaptation disorder is caused by emotional and stressful factors. Stress - the state of tension of adaptation mechanisms. Since the war is still going on in our country, the military often has this nosology. These factors do not endanger a person's physical and mental health, but they do cause a pathological state of negative emotions that disrupts the adaptive response. Critical situations experienced by patients cause distress, which is experienced as grief, unhappiness, exhaustion and is accompanied by a violation of adaptation, control, prevents self-actualization of the individual. Thus, the occurrence of adaptation disorders (AD) in victims of the anti-terrorist operation (ATO), in people with extremely high personal anxiety, stress intensity, social situation in which he operates, personal characteristics of the victim and his biological vulnerability, with serious somatic diseases , disabled people, people who lost their parents in early childhood or lacked maternal care. Vulnerability to the disorder is also increased by premorbid burden of trauma. Clinical manifestations of patients with maladaptation were more often presented in the form of anxiety and depression. Mixed subvariant (anxiety-depressive) meets the diagnostic criteria of heading F 43.22 "Mixed anxiety and depressive reaction" and is characterized by a combination of clinical signs of two options in one patient. The article analyzes various psychological features of AD experience in combatants. It was found that 66.9% of soldiers out of 898 respondents who were demobilized from the ATO zone have pronounced anxiety and depressive symptoms of various degrees. The urgency of this issue is to determine the criteria for psychodiagnostics of the distribution of this condition, which is essential for the treatment of such patients. Purpose: to evaluate the algorithm of clinical psychodiagnostics of AD (F43) on the basis of research of clinical and psychopathological features and pathopsychological characteristics of patients affected by anti-terrorist operation. Mixed anxiety and depressive reaction (F 43.22). Materials and methods: On the basis of the municipal non-profit enterprise "Vinnytsia Regional Clinical Hospital of War Veterans of Vinnytsia Regional Council" (MNE "VRCHWV VRC"), for the period from 2016-2020 898 patients were examined, where the main research methods were: socio-demographic (questionnaire), clinical-anamnestic, clinical-psychopathological (clinical interview), psychodiagnostic, statistical. Results: In the course of this experimental study, the severity of emotional disorders in the study group was determined, data variability was determined and statistical and mathematical analysis of the survey results was performed. There was a significant correlation between indicators of situational, personal, general mental anxiety and depression by Pearson's correlation coefficients (P <0,01). Conclusions: AD occurs as a result of extraordinary events, as well as under the influence of stress, which does not reach an extraordinary or catastrophic level. The development of AD may be preceded by an acute stress reaction. Determining the clinical and psychopathological features of the predominant variants of adaptation disorders in the victims of the ATO is the basis for the development of new diagnostic algorithms and integrated approaches to the treatment of this contingent. With the timely detection of these symptoms, former combatants become less dangerous to others, thus having less traumatic impact on themselves and their families. A good prognosis correlates with the rapid development of symptoms, good social adaptation in premorbid, the presence of social support and the absence of concomitant mental and other diseases.